Administration of the system of municipal solid waste management Lublin experience in the period from 2007 until 2010 - Lutek, Wojciech (Publishing House of Lviv Polytechnic National University, 2016)
This article presents main concepts of building modern system of communal resources management in Lublin. The author indicates major tools used for realisation of the project, describing the results of introducing above mentioned system in the first four years of its functioning (2007–2010).
Keywords: solid waste management; Lublin